OPTIMASI PERTUMBUHAN ISOLAT FUNGI INDIGEN Penicillium sp. LBKURCC153 PENDEGRADASI NAFTALENA MENGGUNAKAN GLUKOSA SEBAGAI KOSUBSTRAT PADA MINIMAL MEDIUM - Aisyah Fitrida; Riryn Novianty; Saryono Saryono; Amir Awaluddin; Nova Wahyu Pratiwi (Jurnal Inovasi Pendidikan dan Sains, 2020)
Naphthalene is one of the pollutants that is difficult to degrade because it belongs to the PAH group and it was carcinogenic. The purpose of this study was to test the effectiveness of an indigenous fungi isolate from Riau Province to degrade naphthalene toxic compounds with glucose as growth cosubstrate. Naphthalene degradation by fungi isolates was influenced by several parameters, including biomass, pH and percentage degradation measured at 0, 4, 8, 12 and 16 days of incubation. Based on biomass parameters, the isolate of Penicillium sp. LBKURCC153 experienced an exponential phase until the 16th day. In the exponential phase, the maximum number of cells increases which shows a positive response to the use of glucose and naphthalene as the carbon and energy source. Isolate decreased their pH from 7 to 3,8, that mean proves the growth activity produce organic acid metabolites of degrade naphthalene. Isolate were also able to degrade naphthalene respectively 27,5% by Penicillium sp. LBKURCC153 in medium with glucose at optimation time until 4 th day incubation. In conclusion, glucose cosubstrate can increase naphthalene degradation percentage by Penicillium sp. LBKURCC153.